ANALISIS ELEMEN VISUAL DAN MASKOT PADA APLIKASI DUOLINGO SEBAGAI MEDIA INTERAKTIF: ANALYSIS OF VISUAL ELEMENTS AND MASCOT IN THE DUOLINGO APPLICATION AS AN INTERACTIVE MEDIA - Marcella Calisya Howard; Wardaya, Marina (Universitas Trisakti, 2025)
Analysis Of Visual Elements And Mascot In The Duolingo Application As An Interactive Media. The development of interactive media, especially educational and entertainment applications highly suggest the importance of engaging visual experiences, which made Duolingo the language learning app to be a great example with its distinctive visual design and the use of a Mascot as its primary identity. This study aims to analyze the visual design elements and the use of Mascot in the Duolingo app as well as to assess the influence in shaping the user's experience and perceptions towards said application's identity. The method used is a qualitative approach through visual content analysis and user interaction, data collected from application documentation which includes the mascots, user interface display and usage patterns then analyzed using Barthes' semiotics framework and multimodal analysis. The finding of this study shows that mascots have an important role as a central visual element that strengthen the appeal of the application, emotional closeness and help facilitate user's recognition of the application's identity. Furthermore visual consistency, including the mascot's colors and forms, blends with user interaction to reinforce an immersive experience. Duolingo shows that the integration of visuals and mascots is not only effective in reinforcing the application's identity but also influences the user's acceptance and emotional connection that provide important implication for the development of the interactive application design in the future. This study also includes a comparative discussion between Duolingo and other educational applications such as Memrise, Babbel, and Busuu to highlight the distinctive role of mascots and visual design in enhancing user motivation and engagement